2021
DOI: 10.1007/s11864-021-00888-3
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned in Managing Patients with Colorectal Cancer During the COVID-19 Pandemic

Abstract: Opinion statement The COVID-19 pandemic forced us to rapidly and dramatically shift our medical priorities and decision making. With little literature or experience to rely on, the initial priority was to minimize patient exposure to the hospital and to others. It remains unclear whether cancer patients are at higher risk of infection or serious complications, or if it is our traditional therapies that place them to be at higher risk. By far, the greatest negative impact was on screening. Routine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…Endoscopic procedure: During the COVID-19 pandemic restrictions there were a significant drop in elective procedures such as screening and diagnostic colonoscopies. Some studies reported a 50% drop in screening and diagnostic colonoscopy procedures[ 9 , 10 , 21 , 24 , 45 , 47 , 49 , 82 ]. This translates to a considerable drop in early diagnosis and endoscopic procedure for T1 lesions amenable to endoscopic resections such as polypectomy, endoscopic mucosal resections or endoscopic submucosal dissection[ 9 , 10 , 21 , 24 , 45 , 47 , 49 , 82 ].…”
Section: Management Of Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopic procedure: During the COVID-19 pandemic restrictions there were a significant drop in elective procedures such as screening and diagnostic colonoscopies. Some studies reported a 50% drop in screening and diagnostic colonoscopy procedures[ 9 , 10 , 21 , 24 , 45 , 47 , 49 , 82 ]. This translates to a considerable drop in early diagnosis and endoscopic procedure for T1 lesions amenable to endoscopic resections such as polypectomy, endoscopic mucosal resections or endoscopic submucosal dissection[ 9 , 10 , 21 , 24 , 45 , 47 , 49 , 82 ].…”
Section: Management Of Colorectal Cancermentioning
confidence: 99%
“…The main aim of treatment is to minimize trauma to the patients, reduce hospital stay and to prevent COVID-19 infection. Respiratory screening should be done before surgery to rule out COVID-19 infection[ 9 , 73 , 79 , 82 , 88 ]. Endoscopic colonic stenting using self-expanding metallic stents should first be attempted in patients with obstruction.…”
Section: Management Of Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the pandemic has led to a widespread deferral of elective procedures, including cancer screenings and surveillance colonoscopies, which are critical for the early detection and management of oncological diseases [ 20 ]. Furthermore, there has been a noticeable disruption in the continuity of care for cancer patients, as many have experienced postponed surgeries or altered chemotherapy protocols, impacting patient outcomes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the necessity of continuing appropriate screening is paramount. Research has been conducted to determine whether delays in the diagnosis and treatment of colorectal cancer impact treatment outcomes, and whether there are viable alternatives when screening is delayed [14,15]. Some studies have reported that treatment delays in colorectal cancer during the COVID-19 pandemic have led to increased mortality rates [16].…”
Section: Introductionmentioning
confidence: 99%